2019
DOI: 10.1136/bmjopen-2018-025556
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic randomised clinical trial of proton versus photon therapy for patients with non-metastatic breast cancer: the Radiotherapy Comparative Effectiveness (RadComp) Consortium trial protocol

Abstract: IntroductionA broad range of stakeholders have called for randomised evidence on the potential clinical benefits and harms of proton therapy, a type of radiation therapy, for patients with breast cancer. Radiation therapy is an important component of curative treatment, reducing cancer recurrence and extending survival. Compared with photon therapy, the international treatment standard, proton therapy reduces incidental radiation to the heart. Our overall objective is to evaluate whether the differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 55 publications
0
44
0
Order By: Relevance
“…Darby et al found that the rate of the incidence of ischemic heart disease increased linearly with the mean heart dose by 7.4% per Gy [13]. In addition, the RADCOMP (Radiotherapy Comparative Effectiveness) trial has also pointed out that the mean heart dose as a critical indicator for cardiotoxicity [45,49]. The mean heart dose of the delivered vIMPT plans in our study was 6.38cGy, which is higher than SPArc 4.5cGy (p=0.04).…”
Section: Discussionmentioning
confidence: 40%
“…Darby et al found that the rate of the incidence of ischemic heart disease increased linearly with the mean heart dose by 7.4% per Gy [13]. In addition, the RADCOMP (Radiotherapy Comparative Effectiveness) trial has also pointed out that the mean heart dose as a critical indicator for cardiotoxicity [45,49]. The mean heart dose of the delivered vIMPT plans in our study was 6.38cGy, which is higher than SPArc 4.5cGy (p=0.04).…”
Section: Discussionmentioning
confidence: 40%
“…[33][34][35][36][37][38][39][40][41] For breast cancer specifically, small series have described significantly reduced cardiac and pulmonary exposures when RT is delivered with photons compared with protons, with particular emphasis on cardiac structures. [20][21][22]42 However, clinicians and national clinical trial protocols 43 continue to base RT planning goals (and, by extrapolation, plan quality) on historical photon constraints. Although it is widely accepted that PBT plans should meet, if not significantly improve, on classical photon dose constraints, new target ranges have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…This was chosen as a relatively comprehensive protocol, intended for patients requiring RNI due to high risk of LRR, but has been found to be complex to follow in practice. The second was the atlas for ClinicalTrials.gov Identifier: NCT02603341 – a Pragmatic Phase III Randomized Trial of Proton vs. Photon Therapy for Patients with Non‐Metastatic Breast Cancer: A Radiotherapy Comparative Effectiveness (RADCOMP) Consortium Trial …”
Section: Methodsmentioning
confidence: 99%
“…Two recent trial guidelines are also worthy of comparison. Following concerns about LRR at the edge or just outside these guidelines, a consortium developed a trial version of RTOG guidelines, here called ‘RADCOMP’, for a Phase III clinical trial comparing the use of photons and protons to treat breast cancer where RNI is required . The Trans‐Tasman Radiation Oncology Group (TROG) Trial 12.02: PET Scans for Locally Advanced Breast Cancer and Diagnostic MRI to Determine the Extent of Operation and Radiotherapy (PET‐LABRABOR) examines the use of PET Scans and MRI to determine extent of operation and RT for locally advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%